Social media as tool for facilitating knowledge creation and innovation in small and medium enterprises. Issue 3 (2nd July 2018) - Papa, Armando; Santoro, Gabriele; Tirabeni, Lia; Monge, Filippo
Abstract : Purpose: The purpose of this paper is to study the effects of social media usage on four knowledge creation processes, namely socialisation, externalisation, combination and internalisation, and innovation in small and medium enterprises (SMEs). Design/methodology/approach: A sample of 96 SMEs has been used to gather data through a standardised questionnaire and test the hypotheses through OLS regression models. Findings: The results indicate that social media influence positively three out of four knowledge creation processes and that they help to foster the innovation process. Originality/value: From a theoretical perspective, the study contributes to literature considering a specific digital tool and its effect on knowledge creation and innovation. In fact, a few studies have considered the impact of social media usage on other variables, such as ROI and productivity, but never on knowledge creation and innovation through a quantitative study. From a managerial perspective, the research suggests managers to implement and involve social media within business and innovation processes.